2020
DOI: 10.3390/agronomy10070966
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Analytical Ultrasound-Assisted Methods for the Extraction of Total Phenolic Compounds and Anthocyanins from Sloes (Prunus spinosa L.)

Abstract: Prunus spinosa L. is a shrub that produces berries—sloes—with a high content of phenolic compounds and anthocyanins. Numerous consumer products are made from sloes, such as “Pacharán” liquors or jams. For these reasons, it is crucial to design accurate analytical methods for the extraction of these bioactive compounds in order to promote their consumption and to improve our health. In this study, an ultrasound-assisted extraction method was developed to extract phenolic compounds and anthocyanins from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 53 publications
4
25
0
Order By: Relevance
“…Furthermore, it was observed that after that time the TPC began to decrease. This fact could be closely related to the degradation of the compounds, as it has been observed in similar matrices such as açai [51], sloe [64] or blackberries [43].…”
Section: Extraction Timementioning
confidence: 53%
See 2 more Smart Citations
“…Furthermore, it was observed that after that time the TPC began to decrease. This fact could be closely related to the degradation of the compounds, as it has been observed in similar matrices such as açai [51], sloe [64] or blackberries [43].…”
Section: Extraction Timementioning
confidence: 53%
“…On the other hand, longer ultrasound times present a considerable reduction in the total amount of anthocyanins extracted (Figure 3), so it is recommended to use ultrasound for short periods of time and under optimal extraction conditions. interaction of the extraction solvent have been previously detected as influential variables also for the extraction of anthocyanins from other similar matrices such as sloe [64], black chokeberry [52] or açai [51]. Furthermore, the relationship between the extraction solvent and the amplitude also turned out to be an influential variable; all of them had a positive coefficient but with a significantly lower influence than that exerted by the extraction solvent.…”
Section: Optimal Conditionsmentioning
confidence: 89%
See 1 more Smart Citation
“…Similarly, the temperature should not be above 70 • C because the solvent would start boiling and this would affect the final recovery. Some authors have observed that percentages of methanol near 70% were more optimal for the extraction of anthocyanins, especially from plant materials [19,35,49]. Finally, higher levels of methanol in the solvent were assayed while the rest of optimal extraction conditions according to the BBD were applied, i.e., 70 • C, 20 mL of solvent per 0.5 g of sample and pH = 5.…”
Section: Optimization Of the Uae Methodsmentioning
confidence: 99%
“…Such designs also provide information on the correlations between the different extraction variables. González-de-Peredo et al [1] optimized an analytical method for the extraction of the total phenolic compounds and anthocyanins from sloes (Prunus spinosa L.) using ultrasound-assisted extraction (UAE). For this purpose, a six-variable response surface design (Box-Behnken) was used.…”
mentioning
confidence: 99%